2013
DOI: 10.1371/journal.pone.0073184
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Circulating Fibroblast Growth Factor 23, α-Klotho, and the Left Ventricular Ejection Fraction and Left Ventricular Mass in Cardiology Inpatients

Abstract: BackgroundFibroblast growth factor 23 (FGF23), with its co-receptor Klotho, plays a crucial role in phosphate metabolism. Several recent studies suggested that circulating FGF23 and α-Klotho concentrations might be related to cardiovascular abnormalities in patients with advanced renal failure.PurposeUsing data from 100 cardiology inpatients who were not undergoing chronic hemodialysis, the association of circulating levels of FGF23, α-Klotho, and other calcium-phosphate metabolism-related parameters with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 48 publications
2
49
0
1
Order By: Relevance
“…Circulating and renal Klotho deficiency precedes the increase in plasma FGF23 25,60 and is a potential mechanism of stimulating FGF23. 17,36 The role of FGF23 in mediation of cardiac hypertrophy was suggested by epidemiologic data 30,[61][62][63] and strongly suggested by an animal study. 30 There may be interactive effects between FGF23 and Klotho.…”
Section: Discussionmentioning
confidence: 96%
“…Circulating and renal Klotho deficiency precedes the increase in plasma FGF23 25,60 and is a potential mechanism of stimulating FGF23. 17,36 The role of FGF23 in mediation of cardiac hypertrophy was suggested by epidemiologic data 30,[61][62][63] and strongly suggested by an animal study. 30 There may be interactive effects between FGF23 and Klotho.…”
Section: Discussionmentioning
confidence: 96%
“…[10,11,15] It has been shown that FGF23 concentrations are elevated in patients who are on dialysis; [10][11][12] , however whether there is an association between FGF23 levels and LVH and other echocardiographic indexes of LV dysfunction in patients who are on dialysis is still unproven. [13,14,16] Therefore, in this study, we decided to evaluate the role of FGF23 on LVH, left ventricular mass index (LVMI), and other echocardiographic findings in a group of patients on hemodialysis without known CVD.…”
Section: Introductionmentioning
confidence: 99%
“…FGF23 levels are found to be increased in the early stages of chronic kidney disease (CKD) 4,5) . The finding that FGF23 levels are associated with cardiac hypertrophy and dysfunction 6,7) suggests that FGF23 represents an independent risk factor for global or cardiac morbidity/ mortality 8,9) . It has been reported that coronary artery calcification (CAC) can be used as a surrogate marker of the total burden of coronary atherosclerosis and that the presence of CAC is associated with peripheral isch-"serum albumin"), and designated as corrected calcium (cCa).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that coronary artery calcification (CAC) can be used as a surrogate marker of the total burden of coronary atherosclerosis and that the presence of CAC is associated with peripheral isch-"serum albumin"), and designated as corrected calcium (cCa). The measurement of FGF23 and -Klotho was performed using enzyme immunoassay kits as described elsewhere 7,24) . The eGFR was calculated by the following Modification of Diet in Renal Disease equation modified for Japanese subjects: eGFR 194 (serum creatinine) 1.094 (age) 0.…”
Section: Introductionmentioning
confidence: 99%